Predicting the impact of secondary macronutrient and micronutrient deficiencies on the responses of potato to site-specific fertilizer recommendations in Rwanda - Mahieu, S. (2024)
Soil fertility limits potato yield in Rwanda. While research towards site-specific fertilizer recommendations for macronutrients (N, P, and K) is ongoing, little is known about secondary macronutrient (Ca, Mg, and S) and micronutrient (B, Fe, Mn, Zn Cu, Mo, and Ni) status in Rwanda. Hence, the aim of this thesis was to investigate the prevalence of secondary macronutrient and micronutrient deficiencies in potato in Rwanda, focusing on site-specific fertilizer validation trials in the agro-ecological zones Birunga, Buberuka Highlands, and Congo-Nile Divide. Potato leave samples were taken on 84 plots during the onset of tuberization and tuber bulking stage, which were analysed for P, K, Ca, Mg, S, B, Fe, Mn, Zn, Cu, Mo, and Ni concentration. The results were compared with critical nutrient concentrations to assess the number of plots with deficiencies. From these same plots, soil samples were taken during the onset of tuberization and analysed for pH, eCEC and exchangeable K, Ca, Mg, and Na. As such, deficiencies could be linked with soil characteristics and trial management data to predict secondary macronutrient and micronutrient deficiencies in different locations. At the onset of tuberization in Birunga, Buberuka Highlands and Congo-Nile Divide, deficiencies were found for Ca in 61, 96, and 87% of plots, for Mg in 0, 2 and 29% of plots, for B in 0, 5.4, and 50% of plots, and for Mn in 18, 23 and 16% of plots, respectively. During tuber bulking, deficiencies were found for Zn in 21, 60, and 5% of plots, and for Cu in 41, 5 and 2% of plots, respectively. Deficiencies of S, Fe, Mo, and Ni were negligible in each agro-ecological zone. Principal component regression with the measured soil characteristics, supplemented by the agro-ecological zones and trial management practices, was performed to predict the concentrations of Ca, Mg, B, Mn, Zn, and Cu. Plant Ca and Mg concentrations were mainly predicted by exchangeable Ca and Mg concentrations and organic matter application. Plant B concentrations were mainly predicted by agro-ecological zone, soil pH, and crop residue removal. Plant Mn concentrations were mainly elevated by application of a Mn-containing fungicide. Plant Zn concentrations were mainly predicted by exchangeable bases and agro-ecological zone. Plant Cu concentrations were mainly predicted by agro-ecological zone. The results can later be linked with digital soil maps to predict deficiencies in other locations. Site-specific application of the deficient secondary macronutrients and micronutrients can then improve NPK fertilizer efficiency and increase potato yields.